Substrate temperature influence on the properties of GaN thin films grown by hollow-cathode plasma-assisted atomic layer deposition - ALEVLİ, MUSTAFA (A V S AMER INST PHYSICS, 2016)
Gallium nitride films were grown by hollow cathode plasma-assisted atomic layer deposition using triethylgallium and N-2/H-2 plasma. An optimized recipe for GaN film was developed, and the effect of substrate temperature was studied in both self-limiting growth window and thermal decomposition-limited growth region. With increased substrate temperature, film crystallinity improved, and the optical band edge decreased from 3.60 to 3.52 eV. The refractive index and reflectivity in Reststrahlen band increased with the substrate temperature. Compressive strain is observed for both samples, and the surface roughness is observed to increase with the substrate temperature. Despite these temperature dependent material properties, the chemical composition, E-1(TO), phonon position, and crystalline phases present in the GaN film were relatively independent from growth temperature. (C) 2015 American Vacuum Society.
Keywords: VAPOR-DEPOSITION; HEXAGONAL GAN; BUFFER LAYER; SAPPHIRE; SILICON; INN; ALN